Key Indicators of the Environment and Natural Resources in the Republic of Kazakhstan - Alibekova A.B.; Sembieva L.M.; Zhagyparova A.O.; Kerimkulova D.D. (SHS Web of Conferences)
This study examines key environmental and natural resource indicators in Kazakhstan, emphasizing their role in sustainable development. The research aims to assess the effectiveness of environmental management strategies and identify critical gaps in resource utilization. The findings indicate that while Kazakhstan possesses significant natural resources, challenges such as pollution, inefficient land use, and climate change threaten ecological stability. The study highlights the need for improved environmental performance indicators, integrating factors like air and water quality, biodiversity conservation, and energy efficiency. A major gap identified is the lack of standardized methodologies for comprehensive environmental assessment, which limits effective policy implementation. The research underscores the importance of adopting integrated environmental auditing and monitoring systems to enhance decision-making processes. Comparative analysis with international environmental frameworks suggests that Kazakhstan should align its policies with global best practices to improve ecological resilience. The implications of this study emphasize the necessity for innovative approaches in environmental management, including green economy initiatives, stricter pollution control measures, and investments in renewable energy. Future research should focus on refining environmental efficiency indicators and developing sustainable resource management models to balance economic growth with ecological preservation.